2002
DOI: 10.1016/s0002-9440(10)64476-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytokeratins 17 and 5 Identifies a Group of Breast Carcinomas with Poor Clinical Outcome

Abstract: While several prognostic factors have been identified in breast carcinoma, the clinical outcome remains hard to predict for individual patients. Better predictive markers are needed to help guide difficult treatment decisions. In a previous study of 78 breast carcinoma specimens, we noted an association between poor clinical outcome and the expression of cytokeratin 17 and/or cytokeratin 5 mRNAs. Here we describe the results of immunohistochemistry studies using monoclonal antibodies against these markers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
416
8
7

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 495 publications
(478 citation statements)
references
References 15 publications
45
416
8
7
Order By: Relevance
“…In conclusion, the study has demonstrated the biological, pathological and clinical features of FABP7 and OATP2 protein expression in human breast carcinoma and with respect to FABP7 particularly its relationship and significance in BP breast cancer [12,13,15,18,22,23,25,28,43,54]. These novel biomarkers have significant associations, both independently and within the BP, on tumour behaviour, expression of other biomarkers, and clinical outcome.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In conclusion, the study has demonstrated the biological, pathological and clinical features of FABP7 and OATP2 protein expression in human breast carcinoma and with respect to FABP7 particularly its relationship and significance in BP breast cancer [12,13,15,18,22,23,25,28,43,54]. These novel biomarkers have significant associations, both independently and within the BP, on tumour behaviour, expression of other biomarkers, and clinical outcome.…”
Section: Discussionmentioning
confidence: 79%
“…The basal-like type or BP of breast cancer has been subject to extensive investigation in recent years, mainly due to its association with poor patient survival [13,15,22,23,43,44]. Despite this interest, there is currently no robust definition for designation of "basal-like" or BP breast cancer in routine clinical practice, furthermore tumours with a BP are also now recognised to exhibit heterogeneity [14,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, there were 23 normal livers and 120 malignant hepatocellular carcinomas, among other control tissues. Tissue arrays were constructed as previously described, 16,17 with core sizes ranging from 0.6 to 2 mm on different arrays. Arrays were scored using a four-tier scale: 0-negative (no staining), 1-equivocal, 2-weak positive (weak to moderate intensity in any percentage of tumor cells), and 3-strong positive (strong intensity in at least 50% of tumor cells).…”
Section: Immunohistochemistrymentioning
confidence: 99%